Agents and Artificial Intelligence Second International Conference, ICAART 2010, Valencia, Spain, January 22-24, 2010. Revised Selected Papers - Filipe, Joaquim; Fred, Ana; Sharp, Bernadette (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Conference on Agents and Artificial Intelligence, ICAART 2010, held in Valencia, Spain, in January 2010. The 17 revised full papers presented together with an invited paper were carefully reviewed and selected from 364 submissions. Same as the conference the papers are organized in two simultaneous tracks: Artificial Intelligence and Agents. The selected papers reflect the interdisciplinary nature of the conference. The diversity of topics is an important feature of this conference, enabling an overall perception of several important scientific and technological trends.